Artificial receptors for nitrate: a comprehensive overview. Issue 44 (4th June 2015) - Dutta, Ranjan; Ghosh, Pradyut
<x xml:space="preserve">Abstract</x> In this feature article, we describe the current status and recent development of synthetic anion receptors for the recognition of nitrate.